SURVEI PELAKSANAAN PEMBELAJARAN PENDIDIKAN JASMANI ADAPTIF SEKOLAH DASAR LUAR BIASA SE-KABUPATEN GUNUNGKIDUL (Department of Physical Education, Sport, Health and Recreation, 2014)
This survey study aimed to figure out the adaptive physical education learning inExtraordinary Elementary Schools of Gunungkidul regency in the academic year2012/2013. This study used a closed questionnaire instrument. The questionnairehad previously been tested. After being valid and reliable, then it was used in thestudy. The population in this study was 9 Extraordinary. The sampling was taken bytotal sampling. The result of the study was the implementation of adaptive physicaleducation learning showed that it had been going well with an average percentageof 84.38%. Implementation of adaptive physical education learning was influencedby three indicators, i.e. a good lesson plan with the percentage of 85.20%, a goodlearning implementation process with the percentage of 84.40%, and a good learningevaluation with percentage 83.30%. Based on the result of this study, it wasconcluded that the implementation of an adaptive physical education learning inExtraordinary Elementary School of Gunungkidul in the academic year 2012/2013had been going well. It can be concluded that the learning model captured throwthe ball using baskets targets to improve learning outcomes captured throw the ball .